Pengaturan Transparansi dan Akuntabilitas Pengelolaan Wakaf Pada BWI Perspektif Maqashid Syari’ah (Studi BWI Provinsi Sumatera Utara) - Zalfa Fadhillah Lubis; Syafruddin Syam (CV Rewang Rencang, 2025)
Transparency and accountability are needed to build and maintain public trust in waqf management. High trust will encourage people to be more active in waqf. One of the obstacles in waqf management is the lack of adequate supervision and transparent reporting. By regulating transparency and accountability, BWI Sumut can improve the supervision system and improve the quality of financial reports and activity reports. The most important Shari'ah maqashid in waqf is the protection of wealth (hifzul mal). Safeguarding wealth is one of the maqasid shariah categorized as maqasid al-dharuriyyah and also includes maqasid ammah, which is Allah's general purpose in making law (shariah). So, in the context of maqashid waqf actually appears as an Islamic instrument in social activities to maintain the role of wealth. So, waqf is in a position to protect property in its interest for a moment, for longer or continuously intended for public waqf.